On Some New Common Fixed Point Results for Finite Number of Mappings in Fuzzy Metric Spaces. (17th August 2022) - Bartwal, Ayush; Ahmad, Junaid; Dimri, R. C.; Prasad, Gopi; Bonyah, Ebenezer
Abstract : We essentially suggest the concept of mutual sequences and Cauchy mutual sequence and utilize the same to prove the existence and uniqueness of common fixed point results for finite number of self- and non-self-mappings using fuzzy ℤ ∗ -contractive mappings in fuzzy metric spaces. Our main result was obtained under generalized contractive condition in the fuzzy metric spaces. We provide examples to vindicate the claims and usefulness of such investigations. In this way, the present results generalize and enrich the several existing literature of the fuzzy metric spaces.